Atlas of Endoscopic Major Pulmonary Resections - Gossot, Dominique; SpringerLink (Online service) (Paris : Springer Paris, 2010)
Video-assisted major pulmonary resections are gaining popularity, as it becomes obvious that minimally invasive surgery is beneficial in terms of reduced postoperative pain, shorted hospital stay, shorter recovery and better compliance to adjuvant chemotherapy, without compromising oncological principles. Different techniques have been described, depending on the use or non-use of an accessory mini-thoracotomy and of endoscopic instrumentation and video display. One of these techniques is the totally endoscopic approach. This technique can prove challenging and tedious because the operating mode and even the anatomical landmarks are different and, in some ways, have to be relearned. The purpose of this atlas is to describe each endoscopic pulmonary lobectomy and segmentectomy step by step, relying on brief technical notes and high-quality still pictures which are orientated and labelled to make them as comprehensible as possible. Each chapter is introduced by an anatomical background which is illustrated by three-dimensional reconstructions. Technical (S0(Btricks(S1 (Band specific dangers are mentioned by pictograms.s
General considerations -- Tips and tricks -- Endoscopic mediastinal lymph node dissection -- Lobectomies -- Right upper lobe -- Middle lobe -- Right lower lobe -- Left upper lobe -- Left lower lobe -- Segmentectomies -- Right upper lobe: apicoposterior segments -- Right lower lobe: superior segment -- Right lower lobe: basal segments -- Left upper lobe: superior segments -- Left upper lobe: lingula -- Left lower lobe: superior segment -- Left lower lobe: basal segments.
Keywords: Medicine; Oncology; Surgery; Endoscopic surgery; Thoracic surgery; Medicine & Public Health; Surgery; Thoracic Surgery; Minimally Invasive Surgery; Oncology